Effects of Lactiplantibacillus plantarum 19-2 on immunomodulatory function and gut microbiota in mice - Wang, Xiaoran; Tang, Jilang; Zhang, Shixia; Zhang, Nuannuan (Frontiers in Microbiology, 2022)
This study aims to evaluate the effects of Lactiplantibacillus plantarum 19-2 (L. plantarum 19-2 ) on mice treated with the alkylating agent cyclophosphamide (CTX). Our findings show that L. plantarum 19-2 restored the spleen and thymus index and the number of white blood cells and lymphocytes% in CTX treated mice. Serum immunoglobulin levels in CTX-treated mice were increased by L. plantarum 19-2. In addition, as compared to the model group, L. plantarum 19-2 up-regulated the content of SIgA, while L. plantarum 19-2 regulates the mRNA and protein expression levels of GATA-3, T-bet, IFN-γ, and IL-4 in small intestinal tissues, which adjusted mucosal barriers, structural status, and the balance of Helper T-cell 1 and Helper T-cell 2. L. plantarum 19-2 regulated the distribution of intestinal flora in mice, promoting the growth of Bacteroides and Proteobacteria. In addition, L. plantarum 19-2 inhibited the growth of several harmful bacteria, including Actinobacteria and Firmicutes.